Metal fabrication technology - Mukherjee, Syamal ([S.l.] : Prentice-Hall of India Pvt.Ltd, 2010)
Designed primarily for undergraduate and postgraduate students of mechanical engineering and production engineering, the book will also be useful for students of engineering diploma programmes in the above fields and certificate courses in metal fabrication and erection, as well as for practising engineers and consultants involved in welding, fabrication, erection, production planning, testing and design. The initial chapters of the book provide an overview of the metal fabrication industry, as well as an exhaustive discussion of the properties of the various engineering materials, heat treatment processes, and frame analysis. The focus then shifts to production planning and control, production line design, as well as drawing, marking and layout. The ensuing chapters explain elaborately the various metal cutting processes, metal forming methods, and manufacturing processes. Assembly and erection, joining and welding, fault analysis and inspection, and metal finishing are covered subsequently. The various systematic guidelines for erection as well as the different prohibited welding methods and welding defects are elucidated. The final chapter of the book is devoted to health and safety issues relevant to fabrication and erection. The book contains numerous illustrations that enable the students to gain a thorough understanding of the subject matter. The review questions at the end of each chapter help to test their comprehension of the underlying concepts.